Crystallization and preliminary X‐ray diffraction analysis of the CRISPR–Cas RNA‐silencing Cmr complex. Issue 6 (1st June 2015) - Osawa, Takuo; Inanaga, Hideko; Numata, Tomoyuki
<x xml:space="preserve">Abstract</x> Clustered regularly interspaced short palindromic repeat (CRISPR)‐derived RNA (crRNA) and CRISPR‐associated (Cas) proteins constitute a prokaryotic adaptive immune system (CRISPR–Cas system) that targets and degrades invading genetic elements. The type III‐B CRISPR–Cas Cmr complex, composed of the six Cas proteins (Cmr1–Cmr6) and a crRNA, captures and cleaves RNA complementary to the crRNA guide sequence. Here, a Cmr1‐deficient functional Cmr (CmrΔ1) complex composed of Pyrococcus furiosus Cmr2–Cmr3, Archaeoglobus fulgidus Cmr4–Cmr5–Cmr6 and the 39‐mer P. furiosus 7.01‐crRNA was prepared. The CmrΔ1 complex was cocrystallized with single‐stranded DNA (ssDNA) complementary to the crRNA guide by the vapour‐diffusion method. The crystals diffracted to 2.1 Å resolution using synchrotron radiation at the Photon Factory. The crystals belonged to the triclinic space group P1, with unit‐cell parameters a = 75.5, b = 76.2, c = 139.2 Å, α = 90.3, β = 104.8, γ = 118.6°. The asymmetric unit of the crystals is expected to contain one CmrΔ1–ssDNA complex, with a Matthews coefficient of 2.03 Å3 Da−1 and a solvent content of 39.5%.